Genome-wide association study and genomic prediction of leaf spot (Stemphylium vesicarium) resistance in spinach diversity panel - Bhattarai, Gehendra; Liu, Bo; Correll, James; Shi, Ainong (Frontiers in Plant Science, 2025)
Stemphylium leaf spot (SLP), caused by Stemphylium vesicarium, has emerged as an increasing threat to spinach production in the United States, with widespread outbreaks reported across major spinach-growing regions over the past two decades. The objectives of this study were to: (1) evaluate global USDA spinach germplasm collections and commercial cultivars for resistance to S. vesicarium; (2) perform genome-wide association studies (GWAS) to identify genomic regions associated with resistance; and (3) conduct genomic prediction (GP) to enhance selection accuracy. A total of 311 diverse spinach genotypes, including USDA germplasm accessions and commercial cultivars, were evaluated under greenhouse conditions at the University of Arkansas using the S. vesicarium isolate Sb-1-St001 from 2019 to 2021. The panel exhibited a wide range of disease responses. GWAS using disease severity index (DSI) values and whole-genome resequencing (WGR)-based SNP markers identified four SNPs—SOVchr1_127757911 (127,757,911 bp, Chr1), SOVchr2_21962694 (21,962,694 bp, Chr2), SOVchr4_114674293 (114,674,293 bp, Chr4), and SOVchr5_37417509 (37,417,509 bp, Chr5)—that were significantly associated with DSI for SLP resistance. Genomic prediction of DSI was performed using seven GP models across nine randomly selected SNP datasets and two GWAS-derived SNP sets. The GWAS-derived marker sets produced higher prediction accuracies in cross-population prediction, with r-values of 0.45 and 0.51 for the 4- and 18-SNP sets, respectively. These results underscore the potential of marker-assisted selection (MAS) and genomic selection (GS) to accelerate the development of spinach cultivars resistant to Stemphylium leaf spot.